Purification and characterization of prostate specific antigen from human urine - Shibata, Kozue; Kajihara, Jun-ichi; Kato, Kazuo; Hirano, Kazuyuki (Biochimica et Biophysica Acta (BBA) - General Subjects, 1997)
Prostate specific antigen (uPSA) was purified to homogeneity from human urine using SuperQ-Toyopearl, Sulfate-Cellulofine, Phenyl-Toyopearl, CM-Sepharose, anti-urokinase IgG Sepharose and Sephadex G-100. The purified uPSA gave a major band at 32.9 kDa on SDS-PAGE under the reduced condition. However, it shows multiple bands on native PAGE. Substrate specificity of purified uPSA is identical with that of PSA from human seminal plasma and uPSA shows the kallikrein and chymotrypsin-like activities. On the analysis of N-terminal amino acid, two amino acid residues at N-terminal position of uPSA were detected and other amino acid sequence of uPSA was identical with that of sPSA. In addition, we isolated the multiple components of uPSA using anion-exchange chromatography. They were almost the same in amino acid composition and N-terminal amino acid sequences and showed differences in lectin-blotting pattern.